2015
DOI: 10.1088/1468-6996/16/2/026001
|View full text |Cite
|
Sign up to set email alerts
|

Electronic conduction in La-based perovskite-type oxides

Abstract: A systematic study of La-based perovskite-type oxides from the viewpoint of their electronic conduction properties was performed. LaCo0.5Ni0.5O3±δ was found to be a promising candidate as a replacement for standard metals used in oxide electrodes and wiring that are operated at temperatures up to 1173 K in air because of its high electrical conductivity and stability at high temperatures. LaCo0.5Ni0.5O3±δ exhibits a high conductivity of 1.9 × 103 S cm−1 at room temperature (R.T.) because of a high carrier conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(38 citation statements)
references
References 84 publications
1
36
1
Order By: Relevance
“…Although the difference in the ionic radii of Co 2+ ions and Zn 2+ ions is very small, Co doping into the ZnO lattice can induce a strain in it and lead to the distortion of the ZnO unit cell . It can be concluded that because of increasing the bond length by a level of doping of 2%, the heat conductivity decreases, whereas the electric conductivity increases, resulting in an increase in charge carriers, and finally, the thermoelectric conversion efficiency (ZT) increases for this system, which makes it possible to use them for thermoelectric applications. The lattice parameters are briefly described in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Although the difference in the ionic radii of Co 2+ ions and Zn 2+ ions is very small, Co doping into the ZnO lattice can induce a strain in it and lead to the distortion of the ZnO unit cell . It can be concluded that because of increasing the bond length by a level of doping of 2%, the heat conductivity decreases, whereas the electric conductivity increases, resulting in an increase in charge carriers, and finally, the thermoelectric conversion efficiency (ZT) increases for this system, which makes it possible to use them for thermoelectric applications. The lattice parameters are briefly described in Table .…”
Section: Resultsmentioning
confidence: 99%
“…In those structures, the octahedral BO6 presents both distortion and rotation that are more important when smaller A-site cations are used. This increases the electrical resistivity and therefore the overall catalytic activity toward oxygen reduction is affected [5,26]. In octahedral BO6 each cation is surrounded by six oxygen anions and, according to the crystal field theory (CFT), d-orbitals split into a lower group of three t2g and a highest group of two eg energy orbitals [27].…”
Section: Introductionmentioning
confidence: 99%
“…The high ionic radius of lanthanum leads to the formation of cubic or a rhombohedral phase, which is considered good for electronic conduction. [ 53,54 ]…”
Section: Resultsmentioning
confidence: 99%